Hands that pray, mine and draw: Collaborative cartography and visual construction of borders in South America (1746) - de Moura, Denise A.S. [UNESP] (Universidade Federal do Rio Grande do Sul, 2022)
In the 18th century, the dispute between the Iberian monarchies for the definition of their territorial limits created a context for the restoration of social alliances on the borders, combining old enemies, such as Jesuits and backwoodsman, in the production of cartographic images that communicated their actions and reiterated their existence in these regions. Such disputes, therefore, foster the development of a visual culture of the sertões outside the official circles of military engineers trained in the academies and hired by the Crowns and inclusive of social agents with field experience and scientific knowledge who worked collaboratively. His images reached the status of supporting document and reached official levels. This conclusion is demonstrated by a letter and map of the lands of the platinum basin made in 1746 and interpreted under the theoretical-methodological guidelines of the sociocultural history of the most recent cartography and which reviews the thesis of cartography as a mere exercise of state power and domination in favor of its understanding as a communicative tool for the rights of other social agents.
Manos que rezan, extraen y dibujan: cartografía colaborativa y construcción visual de fronteras en América del Sur (1746)
Mãos que oram, mineram e desenham: cartografia colaborativa e produção visual de fronteiras na América do Sul (1746)
Keywords: Cartography; Geography; Maps; Religious institutions; Visual materials